Caspase-11 Non-canonical Inflammasomes in the Lung - Oh, Changhoon; Verma, Ambika; Aachoui, Youssef (Frontiers in Immunology, 2020)
The airway epithelium and underlying innate immune cells compose the first-line of host defense in the lung. They recognize pathogen-associated molecular patterns (PAMPs) using membrane-bound receptors, as well as cytosolic receptors such as inflammasomes.Inflammasomes lead to the activation of inflammatory caspases, which in turn process and release the inflammatory cytokines IL-1b and IL-18. Additionally, inflammasomes trigger a form of lytic cell death termed pyroptosis. One of the most important inflammasomes at the host pathogen interface is the non-canonical caspase-11 inflammasome that responds to LPS in the cytosol. Caspase-11 is important in defense against Gram-negative pathogens, and is implicated in inflammatory diseases such as endotoxic shock. However, pathogens can employ evasive strategies to minimize or evade host detection. In this review, we present a comprehensive overview of the function of the non-canonical caspase-11 in sensing of cytosolic LPS, and its mechanism of action with particular emphasis in the lung. We also explore some of strategies pathogens use in the evasion of caspase-11.